Actinomycin D-Activated RNase L Promotes H2A.X/H2B-Mediated DNA Damage and Apoptosis in Lung Cancer Cells - Yin, Huijing; Jiang, Zhengyu; Wang, Shuoer; Zhang, Ping (Frontiers in Oncology, 2019)
Background Chemotherapy is an essential component for comprehensive cancer treatment while drug-resistance usually fails therapy. DNA repair mechanism of cancer cells restrains the efficacy of therapeutics targeting DNA damage. Investigating target inducing irreversible cell death of cancer cells may be promising. Methods The present study used lung cancer cell lines, transplanted tumor model of lung cancers derived from patients with lung adenocarcinoma and molecular experiments to investigate the effects and mechanism of Actinomycin D (Act D) activated RNase L in lung cancers. Results We report RNase L, when activated by Act D, induces Caspase-3/PARP activation. The latter further enables ROCK-1 to initiate subsequent membrane blebbing, and, meanwhile, result in DNA cleavage and cell cycle arrest mediated by H2A.X/H2B-p21 axis, leading to irreversible DNA damage and apoptosis of lung cancer cells. The present study highlighted the crucial role of RNase L in triggering apoptosis mechanism through Caspase-3/ROCK-1/PARP /H2A.X+H2B/p21 axis during Act D treatment. Moreover, activation of RNase L suppressed the tumor formation and the induction of lung cancer stem cells. Conclusion This study unveiled the regulatory function and related mechanism of RNase L and implied the promising application of therapeutics targeting RNase L in lung cancer